Investigation of the Internal Conditions of 213 Reprocessed Endoscopic Channels. Issue 1 (3rd February 2023) - Zhou, Meng-Jiao; Huang, Xi; Liu, Lin-Lin; He, Rong-Pan; Hu, Lu; Xun-Zhang; Zhang, Yan-Xia; Ma, Jiu-Hong
Abstract : Background and Aims: Studies have indicated that endoscope reprocessing failure might be attributed to internal damage or residual liquid in endoscopes. However, large-sample survey data on the internal conditions of endoscopic channels after reprocessing are lacking. This study used a borescope to investigate the internal cleanliness and damage of 213 endoscopic biopsy channels after reprocessing at the endoscopy center of the First Affiliated Hospital of Nanchang University, provided in theoretical basis for the efficacy of endoscope reprocessing and maintenance. Methods: A borescope was used to observe and analyze the inside of the endoscopic biopsy channel of 213 reprocessed endoscopes (in accordance with the Chinese health industry standard "Regulation for cleaning and disinfection technique of flexible endoscope (WS 507-2016). Each endoscope was observed for at least 10 minutes, and the results were recorded and evaluated by 5 researchers independently. Results: In all, 2504 images and 109 videos were recorded, and abnormal findings were classified into 10 categories: scratches (91.5%, 195/213), scratches with adherent peel (46.0%, 98/213), discolored areas (49.3%, 105/213), transparent drops (28.2%, 60/213), milky drops (23.9%, 51/213), white particles (46.9%, 100/213), attached materials (37.6%, 80/213), wear on metal parts (41.3%, 88/213), rust (23.9%, 51/213), and black spots (35.7%, 76/213). Among scratches, those in Teflon from 0-10 cm at the apex of the biopsy channel outlet and in metal from 0-5 cm at the biopsy channel inlet accounted for 58.4% (114/195) and 96.4% (188/195), respectively. Conclusions: Scratches were the most common form of damage in the endoscopic biopsy channels investigated and were related to the use of endoscopic accessories and cleaning brush materials. The incidence of other abnormalities gradually increased with the duration of use and began to increase significantly after 18 months. All abnormalities have a certain impact on the quality of endoscope reprocessing. We recommend that a borescope be used to check the inside of endoscopic biopsy channels regularly to determine the damage and cleaning conditions and that these channels be reprocessed, repaired, or replaced in a timely manner.